Public acceptance of coastal zone management efforts: The role of citizen preferences in the allocation of funds. (24th July 2017) - Evans, Keith S.; Noblet, Caroline L.; Fox, Emma; Bell, Kathleen P.; Kaminski, Abigail
Abstract : We investigate allocation of funds by citizens across management options addressing impairments to coastal water quality. We study systematic variation in citizen allocation of funds to adaptive versus preventative strategies including the impact of referundum choices and test whether allocations will be impacted by cuing in the design of the referendum. Two key policy insights from our results: citizens who vote no on a water quality referendum have different preferences over allocating funds and providing cues to voters influenced allocation behavior. These results can assist decision makers in thinking about language used to communicate coastal water quality issues, particularly budget referenda.